Aesthetics and the cinematic narrative an introduction - Bolus, Michael Peter ca. 20./21. Jh (Anthem Press, 2019)
Since the inception of cinema in the late nineteenth century, filmmakers have employed a wide array of precursory aesthetic strategies in the conception and creation of their disparate works. The existence of these traditional antecedents have afforded filmmakers a diverse range of technical and artistic applications towards the construction of their respective cinematic narratives. Furthermore, the socio-political and cultural contexts in which films are conceived often inform the manner in which particular aesthetic sensibilities are selected and deployed. 'Aesthetics and the Cinematic Narrative' provides a concise historical survey of Aesthetics as a practical philosophical discipline and applies several of its underlying principles to the examination of filmic storytelling